COVID‐19 infection and treatment with hydroxychloroquine cause severe haemolysis crisis in a patient with glucose‐6‐phosphate dehydrogenase deficiency. (7th May 2020) - Beauverd, Yan; Adam, Yannick; Assouline, Benjamin; Samii, Kaveh
Abstract: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is an inherited genetic disorder caused by red cell enzymatic defects and is associated with haemolytic crisis when patients are exposed to oxidative agents (fava beans, drugs, infections). Hydroxychloroquine is suspected to trigger haemolytic crisis in G6PD‐deficient patients, and off‐label administration of this drug to patients infected with the novel coronavirus (SARS‐CoV‐2) could cause concern. We report here the first case of severe haemolytic crisis in a patient with G6PD deficiency, initiated by severe COVID‐19 infection and hydroxychloroquine use. With worldwide spread of COVID‐19, especially in regions with a high prevalence of G6PD deficiency, our case should alert physicians to this possible correlation.